Synthesis, characterization and catalytic performance of cerium dioxide with different morphologies for HCl oxidation - Li, Chenwei; Justus Liebig University Giessen (My University, 2018)
CeO2 represent a promising alternative for the widely used Ru-based catalysts for the HCl oxidation reaction in order to recover Cl2. CeO2 powder has been extensively studied previously, which has clarified the reaction mechanism, the relation between the catalytic activity and feed composition, the reaction temperature, and the Cl coverage on the surface. In general, particles in powder catalysts expose various facets, predominantly low index surfaces with low surface energies. However, correlation between the specific facets and catalytic performance are still unknown. Thus the investigation of catalytic activity and stability over shape-controlled CeO2 nanoparticles (nano-rods, nano-cubes, and nano-octahedrons with exposing preferentially (110), (100), and (111) facets, respectively) is the main research focus of this Ph.D project.This cumulative dissertation comprises two main parts: a literature review which includes the investigation of the HCl oxidation reaction and application of Ce-based catalysts and my research results including two peer-reviewed scientific publications and one completed manuscript to be submitted as scientific publications.The introduction starts with the motivation of HCl oxidation to recover the Cl2 and the investigation over different metal-based catalysts, revealing that CeO2 is a promising catalyst material to replace the industrialized RuO2 catalysts. A brief review of the investigation of shape-controlled CeO2 nanoparticles for some oxidizing reactions indicates that catalysts with specific facets show different catalytic activity and different reaction mechanism. Some studies of doped CeO2 catalysts for enhancing its activity and stability on oxidizing reaction are discussed. Especially, Zr-doped CeO2 nano-particles for the Deacon reaction are discussed explicitly.In the first paper of this Ph.D project, the shape-controlled CeO2 nanoparticles (nano-rods, nano-cubes, and nano-octahedrons) were prepared by hydrothermal method and their activity and stability were investigated for HCl oxidation reaction under two reaction conditions (mild: Ar:HCl:O2 = 7:1:2 and harsh: Ar:HCl:O2 = 6:2:2). Several kinds of characterizations (X-ray Diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Transmission electron microscopy (TEM), Scanning electron microscope (SEM), and Oxygen storage capacity (OSC)) were performed for the as prepared CeO2 catalysts to investigate their physicochemical properties and how these properties affect the catalytic activity and stability. It turned out that nano-rods are mostactive in terms of the Space time yield (STY), followed by the cubes and finally the octahedrons. The very same trend is reconciled with the Complete Oxygen Storage Capacity (OSCc) with the rods having the highest OSCc and the octahedrons having lowest one. Regarding the stability of these catalysts ex-situ characterizations were conducted after the HCl oxidation reaction by various techniques (i.e. XRD, XPS, and TEM). XRD showed the changes of bulk structures (i.e. formation of hydrate CeCl3 crystal phase for the CeO2 nano-cubes and CeO2 nano-octahedron catalysts under harsh condition). Rietveld refinement of the XRD data discriminated the mixed phases and quantified the concentration of the crystal phase of CeCl3·nH2O, presenting the degree of chlorination. The surface compositional and morphological changes were addressed by XPS and TEM, respectively. The results indicated that rods are stable without any morphology change under harsh condition, while cubes and octahedrons are unstable, as can be determined by the destruction of their morphology and the forming the crystal phase of hydrate CeCl3. However, for the mild reaction condition, all the catalysts are stable.In the second paper we systematically investigated the catalytic stability as a function of temperature in order to clarify the correlation between the chlorination degree and the reaction temperature. A simple theoretical model based on pure thermodynamics for the chlorination of the catalyst to validate the experimental data. To visualize morphological changes and the phase transformations, the shape-controlled CeO2 nano-cubes with facets of preferential (100) orientation were fabricated. Due to crystallinity of the formed CeCl3·nH2O phase, the degree of chlorination was quantified by the Rietveld refinement. The results showed that CeO2 is substantially chlorinated below 380 °C, revealing a low catalytic activity originated from the hydrate CeCl3. While both the activity and chlorination degree change abruptly at 390 °C. Based on the model of chlorination for CeO2, we discovered that the leading driving force for the chlorination is the formation of the side product H2O. Thus, adding a small amount (1 %) of H2O into the feed gas stream can essentially remove the driving force for chlorination, thereby improving the catalytic stability. This modelling result, evidenced by our experiment data, is not only helpful for understanding the catalytic mechanism of our catalytic system but might also be extended to other heterogeneously catalysed oxidation reactions, in particular where H2O is formed as a by-product.In the third paper, mixed Ce1-xZrxO2 (x = 2 %, 5 % and 20 %) nano-rods were successfully synthesized and were exposed to HCl oxidation reaction for 24 h under different reaction mixture(10% O2, 20%-30% HCl and balanced with Ar) at 430 °C to investigate their stability. For Pure CeO2 nano-rods bulk chlorination already started at reaction mixtures of HCl:O2 > 2, thus revealing a lower stability and a dramatic loss in activity. CeCl3·nH2O was formed via nucleation and growth forming large single crystalline particles. A doping of 5 % Zr for the mixed Ce1-xZrxO2 catalysts already efficiently suppressed the bulk chlorination for a reaction mixture of Ar:HCl:O2 = 6.5:2.5:1. XPS measurements revealed that the chlorine concentration is too high to be solely assigned to on-surface chlorine. Additional XPS measurements conducted after an oxygen plasma treatment verified that some of Cl penetrated into the near surface region. For even harsher reaction conditions (i.e. Ar:HCl:O2 = 6:3:1) none of these Ce1-xZrxO2 catalysts were stable at 430 °C. However, even pure CeO2 nano-rods were stable under such harsh reaction conditions when the reaction temperature was set to 500 °C.
Keywords: HCl oxidation; Ceria nano particles; different morphologies; ddc:540